2017
DOI: 10.1038/pr.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal exposure to intermittent hypoxia in rodents is proinflammatory, impairs white matter integrity, and alters brain metabolism

Abstract: BackgroundPreterm infants are frequently exposed to intermittent hypoxia (IH) associated with apnea and periodic breathing that may result in inflammation and brain injury that later manifests as cognitive and executive function deficits. We used a rodent model to determine whether early postnatal exposure to IH would result in inflammation and brain injury.MethodsRat pups were exposed to IH from P2–P12. Control animals were exposed to room air. Cytokines were analyzed in plasma and brain tissue at P13 and P18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…In parallel, we examined the hippocampal synaptic plasticity by measuring long term potentiation (LTP), that might underlie observed memory deficits, as well as structural changes and myelination in white matter in adult mice exposed to severe episodes of IH as neonates. White matter injury is a consistent finding in perinatal brain hypoxia and ischemia injury of different types (Cai et al, 2012; Juliano et al, 2015; Darnall et al, 2017; Oorschot et al, 2013) and may also be a determinant of later cognitive abnormalities. Impairments in LTP have been examined in models of single acute hypoxic event during prenatal period (Fleiss et al, 2011), but have not been studied in neonatal IH, especially in relation to cognitive outcome.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In parallel, we examined the hippocampal synaptic plasticity by measuring long term potentiation (LTP), that might underlie observed memory deficits, as well as structural changes and myelination in white matter in adult mice exposed to severe episodes of IH as neonates. White matter injury is a consistent finding in perinatal brain hypoxia and ischemia injury of different types (Cai et al, 2012; Juliano et al, 2015; Darnall et al, 2017; Oorschot et al, 2013) and may also be a determinant of later cognitive abnormalities. Impairments in LTP have been examined in models of single acute hypoxic event during prenatal period (Fleiss et al, 2011), but have not been studied in neonatal IH, especially in relation to cognitive outcome.…”
Section: Introductionmentioning
confidence: 84%
“…Several rodent models have been developed to study effects of IH on brain development. In animal models that mimic clinical situation of relatively mild IH, characterized by small magnitude of desaturations and no bradycardia, very few long term cognitive abnormalities are reported (Cai et al, 2012; Juliano et al, 2015; Darnall et al, 2017). Moreover, mild IH is also reported to improve cognitive performance (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research also suggests that these similar intermittent oxygen desaturations are not benign in preterm infants. Darnall et al demonstrated in a rat model designed to mimic the IH that occurs in association with apnea of prematurity that IH was associated with acute changes in systemic and brain parenchymal inflammatory cytokines and evidence of central nervous system injury. With regard to human studies Horne et al documented that apneic events persist in preterm infants through the first 6 months post term‐equivalent and are associated with decreases in cerebral oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Short averaging times are needed to detect repetitive short apnoeas such as those seen in periodic breathing. Evidence for the adverse effects of these repetitive dips in saturation on developmental outcome of neonates remains lacking, but animal studies and those in older children support a detrimental effect on brain tissue. Thus, detection of repetitive dips provides important information to guide treatment decisions such as timing of discontinuation of supplemental oxygen.…”
Section: Discussionmentioning
confidence: 99%